2018
DOI: 10.3889/oamjms.2018.303
|View full text |Cite
|
Sign up to set email alerts
|

Improving Nursing Care Documentation in Emergency Department: A Participatory Action Research Study in Iran

Abstract: BACKGROUND:Standardization of documentation has enabled the use of medical records as a primary tool for evaluating health care functions and obtaining appropriate credit points for medical centres. However, previous studies have shown that the quality of medical records in emergency departments is unsatisfactory.AIM:The aim of this study was improving the nursing care documentation in an emergency department, in Iran.MATERIAL AND METHODS:This collaborative action research study was carried out in two phases t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 17 publications
0
13
0
5
Order By: Relevance
“…Studies on nursing documentation in Iran have focused more on the quality of nursing documentation. These studies have reported the quality of nursing documentation was unsuitable and did not contain necessary information (Tabrizi et al, 2016; Vafaei, Manzari, Heydari, Froutan, & Farahani, 2018). These studies reviewed the nursing records of patients based on nursing activities though they did not pay attention to patient care needs and the documented nursing diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on nursing documentation in Iran have focused more on the quality of nursing documentation. These studies have reported the quality of nursing documentation was unsuitable and did not contain necessary information (Tabrizi et al, 2016; Vafaei, Manzari, Heydari, Froutan, & Farahani, 2018). These studies reviewed the nursing records of patients based on nursing activities though they did not pay attention to patient care needs and the documented nursing diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…These weaknesses have similarly been highlighted in many other studies. [ 21 22 23 24 25 26 27 ] Studies have identified factors such as time constraint, attitude of the midwives, availability of few numbers of midwives in a shift[ 5 6 ], and no emphasis from the administrators[ 19 ] to influence the incomplete LR documentation. A qualitative study on maternity care in secondary level public health facilities of Uttar Pradesh, has highlighted the availability of infrastructure, human resources, supplies, and medicines as critical for quality improvement in service delivery.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] It helps in qualitative assessment of records during medical jurisprudence, death audits, and case review. [ 6 7 ] Availability and maintenance of a good documentation system is also critical for facility level review of records. [ 8 ] However, there exist gaps towards adherence and completeness in LR documentation.…”
Section: Introductionmentioning
confidence: 99%
“…Embora a MOP se baseie em um dos modelos mais antigos de gestão da mudança, ela se aplica ao contexto contemporâneo e consiste em alicerce para os processos de mudança no contexto da saúde e da enfermagem, sendo atual para os dias de hoje (3,(13)(14)(15)(16)(17)(18)(19)(20) .…”
Section: A Mop Como Método De Pesquisa Eintervenção Na Produção Do Counclassified
“…No que diz respeito a esses estudos, destacamos alguns que apontam resultados positivos na gestão de mudanças. Estudo realizado no Irã (20) demonstrou práticas mais apropriadas para melhorar a documentação dos cuidados de enfermagem. Na perspectiva dos autores, a participação dos profissionais, a responsabilidade gerencial, a adesão dos enfermeiros aos padrões de documentação, a melhoria do estilo de liderança e o monitoramento e controle contínuos foram importantes ganhos da investigação.…”
Section: Efeitos Do Uso Da Mop No Contexto Da Enfermagem E Saúdeunclassified